Salivary levels of TNF-α in patients with recurrent aphthous stomatitis: A cross-sectional study - Kanad Chaudhuri; Keerthi Krishnankutty Nair; Lingappa Ashok (Tabriz University of Medical Sciences, 2018)
Introduction: Recurrent aphthous stomatitis (RAS) is a disorder characterized by recurring ulcers involving the oral mucosa in patients with no other signs of disease. The current concept of etiopathogenesis is that RAS is a clinical syndrome with several possible etiologies. The process seen in RAS is probably initiated through an as yet unidentified antigenic stimulation of the mucosal keratinocytes, which stimulates secretion of T- cell activation cytokines- Interleukins and Tumour necrosis factor alpha (TNFα). TNFα causes inflammation by its effect on endothelial cell adhesion and neutrophil chemotaxis. The relevance of TNFα to the pathogenesis of RAS has stemmed from the observations that anti- TNFα drugs such as thalidomide and pentoxifylline have been found to be effective in the treatment of RAS. Therefore, the present study is an attempt to measure the levels of salivary TNFα in patients with RAS which will reflect the local production of cytokines at the site of the disease. Aim: To evaluate the salivary levels of TNFα in patients with recurrent aphthous stomatitis. Materials and Methods: The study comprised of 60 subjects, of whom 30 clinically proven RAS patients of either sex were selected as cases and 30 healthy, age & gender-matched subjects were selected as controls. After taking informed consent, 5 ml of unstimulated saliva was collected from both the study and control group. Determination of salivary TNFα levels was done by Enzyme-Linked Immunosorbent Assay (ELISA) and expressed in picograms per milliliter (pg/ml). The statistical analysis of the RAS group and the control group were done using unpaired t-test. Gender wise comparison of salivary TNFα levels in the study and control groups was done using one-way ANOVA test. Results: There was statistically highly significant increase in the mean salivary TNFα levels in the RAS group compared to the control group (p < 0.001). It was also revealed that the mean salivary TNFα levels in females were more than males in the study group and this difference was statistically significant (p <0.05). Conclusion: It is fair to suggest that TNFα plays a very important mediatory role in the pathogenesis of RAS and may play an important role in the search for a definitive treatment for the disease.